Biotechnological potential of impacted scenarios for the restoration of TBT contaminated environments - Monteiro, Hugo (2011)
Tributyltin (TBT) is an organotin compound commonly used as an antifouling agent in marine paint formulations. Due to its wide industrial application and its consequent discharge into the environment, TBT pollution is recognized as major environmental problem at a global scale, being recently considered to be the most toxic substance ever introduced into the marine environment. Microorganisms from historically contaminated sites are able to tolerate pollutants and even degrade them, which may be a key factor in the restoration of contaminated environments. Nevertheless, byproducts resulting from the degradation process might be more or less toxic than the parent compound to ecological relevant species. The determination of the substance presence by analytical chemistry, although essential, may not present ecological relevance, as it might not be related to its ecotoxicity. In this study, TBT-resistant bacteria collected from 7 Portuguese ports (Póvoa de Varzim, Leixões, Aveiro, Figueira da Foz, Peniche, Setúbal and Sines) were isolated in increasing concentrations of the toxicant (0.1, 1, and 3mM of TBT) and those growing at the highest concentration were characterized by genomic fingerprinting (REP-PCR) and tested as potential bioremediation tool in laboratory contaminated media. The percentage of TBT-resistant isolates varied between 0.08% (Setúbal harbor) and 7.67% (Peniche). REP-PCR analysis revealed a total 111 distinct genetic profiles, being Peniche the location with lower variability while Figueira da Foz had the highest variability. Selected isolates were used to bioremediate waters contaminated waters, and their potential as bioremediation tools was assessed through ecotoxicological testing with the gastropod Gibbula umbilicalis. Ecotoxicological testing suggested that some TBTresistant bacteria are able to reduce the toxicity of TBT contaminated waters. This study contributed to the understanding of TBT resistance, however more intensive and focused research in the area of TBT bioremediation mediated by marine bacteria is still needed, particularly on the mechanisms behind TBT resistance and on the identification of pathways and genes responsible for TBT degradation.